Education on Screen Time Management to Enhance Awareness and Knowledge for Supporting the Optimal Development of 5-Year-Old Children - Lailaturohmah; Nelly Nugrawati; Ayu Wijaya; Sri Utami Subagio; Andi Muhammad Adam (CV. Get Press Indonesia, 2024)
Uncontrolled screen time duration can negatively impact the development of 5-year-old children. This community service activity aims to provide education on screen time management to support their optimal development at TPA Al Amiin, Kediri City. Through socialization, training, and mentoring methods for parents and caregivers, this initiative increases awareness of the adverse effects of excessive screen time and provides practical strategies for managing it wisely. The effectiveness of the training was evaluated using pre-tests and post-tests, revealing a significant improvement in participants’ knowledge, with an average pre-test score of 60% and a post-test score of 88%. The results suggest that structured education on screen time management plays a crucial role in supporting the optimal development of 5-year-old children and can serve as an intervention model applicable in other early childhood education setting.